Mixed reality learning spaces for collaborative experimentation: A challenge for engineering education and training - Müller, Dieter; Bruns, F. Wilhelm; Erbe, Heinz-Hermann; Robben, Bernd; Yoo, Yong-Ho (International Journal of Online and Biomedical Engineering (iJOE), 2007)
Although the vast majority of research in human-computer interaction involves only our senses of sight and hearing, with sporadic forays into touch, future laboratories used in engineering education will mostly benefit from developments beyond video and sound. Tangible and embedded interaction, augmented and mixed reality characterizes ultimate technologies for further applications in collaborative remote engineering and lab work. This paper presents our latest research to facilitate collaborative experimentation with such innovative technologies. Our vision is a collaborative learning space, which involves an amalgam of real, virtual and remote lab tools to support a wide spectrum of simple and complex, concrete and abstract, safe and dangerous experimentation settings. We will review related concepts and discuss lessons learned from our research and prototype development. Recent work involves the use of mixed reality (as opposed to â??pureâ?? virtual reality) techniques to support seamless collaborative work between remote sites. We describe this and identify areas for future research.